Finances and credit: problems, conceptions, management - University of Latvia. Department of Economics and Management, Institute of Finance; Zelgalvis, Elmārs (University of Latvia, 2001)
Economic situation in the Baltic States is investigated, in particular the development of economics in transition is analysed in Latvia, Lithuania, Estonia and Poland. There are studied the following details: Monetary and exchange rate policy; Crediting and bank management; Development of securities market; Management of taxes and finance; Development of accounting policy; Pension reform perspective etc.
Finanses un kredīts: problēmas, koncepcijas, vadība
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics; Monetary policy; Exchange rate; Credit; Banks and banking; Securities market; Taxes; Accounting policy; Pension reform; Monetārā politika; Bankas un banku darbība; Kredīti; Fiskālā politika